Ecological and biogeographical studies on the rocky shore seagrass Thalassodendron ciliatum (Forsskal) den Hartog and its seaweed epiphytes at the southern limit of its distribution in the western Indian Ocean by Catherine Margot Browne. - Browne, Catherine Margot (Department of Biological Sciences, 2014)
Includes abstract.